Addition of Sesamol Increases the Oxidative Stability of Beeswax Organogels and Beef Tallow Matrix Under UV Light Irradiation and Thermal Oxidation. Issue 5 (16th April 2019) - Hong, Seungmi; Jo, Seungbeen; Kim, Mi‐Ja; Park, Sungkwon; Lee, Suyong; Lee, Jonggil; Lee, JaeHwan
Abstract: To enhance the oxidative stability of organogels made from canola oil, 40 ppm sesamol was added to beeswax‐based organogels stored under ultraviolet (UV) light irradiation and 60 or 100 °C thermal oxidation conditions. To study the practical application of organogels as animal fat substitutes, beef tallow was mixed with organogels and their oxidative stability was determined under oxidative stress conditions. Without sesamol addition, the organogels and beef tallow with organogel oxidized rapidly under UV irradiation and thermal oxidation. The addition of 40‐ppm sesamol decreased the consumption of headspace oxygen and the formation of primary and secondary oxidation products significantly ( P  < 0.05) compared with those in samples without the addition of sesamol, irrespective of oxidative stress. Sesamol improved the oxidative stability of organogels and beef tallow with organogel, which could be used in the meat industry. Practical Application: Organogels may replace trans ‐fat or highly saturated lipids in food products. The high degree of unsaturation and processing temperature mean that antioxidants are needed to extend the shelf life of organogels or organogel‐containing products. The addition of sesamol significantly enhanced the oxidative stability of organogels and of beef tallow‐containing organogels under UV irradiation and thermal oxidation conditions. Therefore, sesamol‐supplemented organogels could replace saturated fats in beef tallow and prolong the shelf‐life of meat products.